Peranan elemen store atmosphere terhadap keputusan pembelian pada masa pandemi Covid-19 - Ash Shadiq Egim; Dwi Hasti Okta Murti (Jurnal Kajian Manajemen dan Wirausaha, 2022)
The aim of this study is to investigate (1) The effect of Exterior on purchasing decisions at McDonald's Padang outlets. (2) the effect of General Interior on purchasing decisions at McDonald's Padang outlets. (3) the influence of Store Layout on purchasing decisions at McDonald's Padang outlets. (4) the effect of Interior Display on purchasing decisions at McDonald's Padang outlets. The analysis technique used in this research is quantitative with multiple linear regression analysis. The population in this study are consumers who have made purchases at McDonald's Ahmad Yani Padang branch with 97 respondents as research samples by conducting a survey of consumers at McDonald's Ahmad Yani Padang branch. The results of the study prove that the four elements of the store atmosphere consisting of the store interior, general interior, store layout, and interior display have a positive and significant effect on purchasing decisions at McDonald's Ahmad Yani Padang branch. The store exterior variable is the most significant variable.